Business Development Strategy in Furniture Business Using Business Model Canvas Approach - Mardhiyah, Ainun; Khairifa, Feni (LifeSciFi, 2024)
Business Model Canvas (BMC) has a Customer Segment element in the furniture business, namely the upper middle class and specialized. The research aims to find out the furniture business strategy implemented by BMC. The study used a qualitative descriptive method by conducting interviews with informants, namely furniture owners and employees. The results of the study used 9 (nine) BMC elements. The customer segment is from the upper middle class and specialized value Proposition, namely the value of loyalty to provide the best and guarantee quality. The channel uses online and offline media. Customer Relationships build excellent and effective communication. Revenue stream from the sale of products produced. Key Activities purchase quality raw materials and processed labour and distribute them using supporting resources. Key Partners use vendors who provide raw materials and e-commerce parties. Key Resources look for raw material resources for labor to process. The cost structure consists of fixed costs and variable costs. Research implications can contribute to furniture entrepreneurs in Indonesia and internationally, especially Medan City. Using BMC to find strengths and weaknesses to get a solution. The results of using BMC increase productivity and welfare.